2015
DOI: 10.15193/zntj/2015/98/014
|View full text |Cite
|
Sign up to set email alerts
|

Basic Chemical Composition, Content of Micro- And Macroelements and Antio Xidant Activity of Different Varieties of Garlic’s Leaves Polish Origin

Abstract: S t r e s z c z e n i eThe aim of this study was to comparison of chemical components and antioxidant activity in leaves of winter and spring varieties of garlic, obtained from POLAN Company; Krakow, Poland) as well as in leaves of wild (bear's) garlic. The content of basic chemical components were determined according to the AOAC methods. Selected minerals content was determined according to the PN procedure. Vitamin C and polyphenols were determined using the Tillman's and Folin-Ciocalteau's methods, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 30 publications
8
27
4
1
Order By: Relevance
“…Total polyphenol concentration and antioxidant activity were significantly higher in the Harnaś and Ornak cultivars harvested in May as compared with samples harvested in other months ( Table 2). This is in line with the lower level of polyphenolic compounds in mature leaves of Harnaś and Ornak cultivars reported by Piątkowska et al [13]. Chen et al [9] reported a much higher concentration of polyphenolic compounds and antioxidant activity measured with the DPPH method (12.64 to 22.66 mg/1 g gallic acid, 9.92 to 40.41 µmol Trolox/g) in garlic bolts and cloves from cultivars of Chinese origin (17.16 to 42.53 mg/1 g gallic acid, 4.30 to 32.02 µmol Trolox/g).…”
Section: Selected Bioactive Compounds Concentrationsupporting
confidence: 91%
See 4 more Smart Citations
“…Total polyphenol concentration and antioxidant activity were significantly higher in the Harnaś and Ornak cultivars harvested in May as compared with samples harvested in other months ( Table 2). This is in line with the lower level of polyphenolic compounds in mature leaves of Harnaś and Ornak cultivars reported by Piątkowska et al [13]. Chen et al [9] reported a much higher concentration of polyphenolic compounds and antioxidant activity measured with the DPPH method (12.64 to 22.66 mg/1 g gallic acid, 9.92 to 40.41 µmol Trolox/g) in garlic bolts and cloves from cultivars of Chinese origin (17.16 to 42.53 mg/1 g gallic acid, 4.30 to 32.02 µmol Trolox/g).…”
Section: Selected Bioactive Compounds Concentrationsupporting
confidence: 91%
“…Protein and ash content decreased during plant maturation. Protein concentration in garlic grown from air bulbils, in our study, was significantly lower than in the mature garlic leaves of Harnaś and Ornak cultivars [13]. Furthermore, the same authors have reported four times higher concentration of ash in the garlic leaves of Harnaś and Ornak (14.1 and 13.1 g/100 g DM, respectively) harvested in July than in our samples of these cultivars harvested during the same month [13].…”
Section: Proximate Analysiscontrasting
confidence: 51%
See 3 more Smart Citations